Strong correlations and orbital texture in single-layer 1T-TaSe2 - Chen, Yi; Ruan, Wei; Wu, Meng; Tang, Shujie; Ryu, Hyejin; Tsai, Hsin-Zon; Lee, Ryan L.; Kahn, Salman; Liou, Franklin; Jia, Caihong; Albertini, Oliver R.; Xiong, Hongyu; et al. (Nature physics, 2020)
Strong electron correlation can induce Mott insulating behaviour and produce intriguing states of matter such as unconventional superconductivity and quantum spin liquids. Recent advances in van der Waals material synthesis enable the exploration of Mott systems in the two-dimensional limit. Here we report characterization of the local electronic properties of single- and few-layer 1T-TaSe 2 via spatial- and momentum-resolved spectroscopy involving scanning tunnelling microscopy and angle-resolved photoemission. Our results indicate that electron correlation induces a robust Mott insulator state in single-layer 1T-TaSe 2 that is accompanied by unusual orbital texture. Interlayer coupling weakens the insulating phase, as shown by reduction of the energy gap and quenching of the correlation-driven orbital texture in bilayer and trilayer 1T-TaSe 2 . This establishes single-layer 1T-TaSe 2 as a useful platform for investigating strong correlation physics in two dimensions. The electrons that contribute to the Mott insulator state in single-layer 1T-TaSe2 are shown to also have a rich variation in their orbital occupation. As more layers are added, both the insulating state and orbital texture weaken.